ANALISIS KEMAMPUAN INTRINSIK SABANG SEBAGAI PORT OF CALL KAPAL PESIAR - Nanda, Riska; Baiquni, Muhammad; Muhammad, Muhammad (JURNAL MASTER PARIWISATA, 2023)
Sabang is one of the 18 entrances for foreign tourist ships that are required to meet a number of characteristics. In determining a destination, cruise liners pay attention to a number of issues, both in terms of port facilities and the availability of various tourist attractions at the destination. This study aims to examine the intrinsic capabilities of Sabang as a cruise ship destination by assessing 14 port of call indicators. The results showed that 13 of the indicators were available in Sabang, 1 other indicator related to night entertainment could not be provided because it was against the norms and the Shari'a in Aceh. On the other hand, the cultural potential in Sabang can be an alternative to entertainment demands for cruise ship tourists. Keywords: intrinsic capabilities; port of call destinations; cruise ship tourism.